Comparative Study of Dynamic Susceptibility Contrast Perfusion MR Images between Warthin's Tumor and Malignant Parotid Tumors - Shin Young Park; Hak Jin Kim; Wonjae Cha (Kosin Medical Journal, 2019)
Objectives To identify diagnostically meaningful differences between Warthin's tumor and malignant masses in the parotid gland by dynamic susceptibility contrast (DSC) MR imaging. Methods Eleven malignant parotid tumors and 9 Warthin's tumors were included. MR imaging was performed on all patients. Signal intensity time curves of tumors were obtained by DSC MR imaging and dynamic susceptibility contrast percentages (DSC%) were calculated. Results No significant difference was observed between malignant tumors and Warthin's tumors (P = 0.437), although DSC% values tended to be higher for Warthin's tumors. Conclusions Warthin's tumor tended to have higher DSC% values than malignant parotid tumors, but this difference was not significantly different.